TextSortenkriterien für Werbematerialien technischer Unternehmen. Texttyp: technical prospect - Wielińska, Katarzyna (Glottodidactica, 2005)
The paper refers to the basic problems of classification of technical prospects to particular text types. On the basis of three different prospects the author makes an attempt of describing some of classifications methods and factors relevant for translation orientated text analysis. Defining conditions of classification of this popular text type can prove to be helpful for its future translators.